Vitamin D Deficiency in Patients with Central Retinal Vein Occlusion: A Case Control Study. (4th March 2017) - Epstein, David; Kvanta, Anders; Lindqvist, Pelle G.
ABSTRACT: Purpose : Central retinal vein occlusion (CRVO) has been shown to occur more often in winter/spring season. We aimed to evaluate if patients with CRVO have more vitamin D deficiency compared to matched controls. Methods : Prospective match controlled study of 72 patients with CRVO and 144 matched controls. All new CRVO cases presenting at St. Erik Eye Hospital, Stockholm, Sweden during the study period were approached to participate. Statistics Sweden provided randomly selected controls matched for age, gender, and season. The first 18 cases of CRVO and 36 controls for each of the four seasons were included and blood was drawn for 25-OH vitamin D analysis (25(OH)D). Results : About half of the patients (51.4%) in the CRVO group had vitamin D deficiency [25(OH)D < 50 nmol/l] as compared to 39.3% in the control group [odds ratio 1.64, 95% confidence interval (CI) 0.91–2.94]. The mean concentrations of serum 25(OH)D were 55.3 nmol/l (95% CI 48.4–62.2) in the study group and 59.8 nmol/l (95% CI 55.4–64.2) in the control group ( p = 0.28). In stratified analysis, the CRVO patients under 75 years had significantly lower 25(OH)D levels than the matched controls (47.8 nmol/l vs. 59.0 nmol/l, p = 0.02). Conclusions : Vitamin D deficiency is common in patients with CRVO. No significant differences in vitamin deficiency or 25(OH)D levels were found in comparison to the control group. However, the CRVO patients under 75 years had significantly lower 25(OH)D levels as compared to the control group.